2020
DOI: 10.1093/biosci/biaa067
|View full text |Cite
|
Sign up to set email alerts
|

Global Cropland Connectivity: A Risk Factor for Invasion and Saturation by Emerging Pathogens and Pests

Abstract: The geographic pattern of cropland is an important risk factor for invasion and saturation by crop-specific pathogens and arthropods. Understanding cropland networks supports smart pest sampling and mitigation strategies. We evaluate global networks of cropland connectivity for key vegetatively propagated crops (banana and plantain, cassava, potato, sweet potato, and yam) important for food security in the tropics. For each crop, potential movement between geographic location pairs was evaluated using a gravit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 108 publications
(127 reference statements)
0
34
0
Order By: Relevance
“…The efforts of GHUs in thoroughly testing germplasm accessions for known pests, before their release for international transfer, have averted the inadvertent spread of quarantine pests. This is of great significance, as most CGIAR centers operate in countries where some of the most dreaded pests are prevalent (e.g., cassava brown streak virus, Karnal bunt, maize lethal necrosis, rice blight, and wheat blast, to name a few) [ 82 ]. Years of experience indicate that adaptability is a vital requirement for sustaining operations in an era of constant changes driven by pest outbreaks, agricultural intensification, climate variability, phytosanitary policies, and regulations [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The efforts of GHUs in thoroughly testing germplasm accessions for known pests, before their release for international transfer, have averted the inadvertent spread of quarantine pests. This is of great significance, as most CGIAR centers operate in countries where some of the most dreaded pests are prevalent (e.g., cassava brown streak virus, Karnal bunt, maize lethal necrosis, rice blight, and wheat blast, to name a few) [ 82 ]. Years of experience indicate that adaptability is a vital requirement for sustaining operations in an era of constant changes driven by pest outbreaks, agricultural intensification, climate variability, phytosanitary policies, and regulations [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study on the patterns of invasion and spread pathways of 1517 invasive species reported that horticulture and the nursery trade are the dominant pathways for the incursion of invasive alien species [ 84 ]. The increasing international exchanges and the globalization of the world present a high risk that introduced pests will be established and expand quickly [ 82 ]. Safe and efficient germplasm transfer forms a critical preventive pest control approach for the CGIAR programs under the IPPC treaty and national laws.…”
Section: Discussionmentioning
confidence: 99%
“…Previous models that describe or predict the extent of disease spread and velocity of epidemics assume dispersal is isotropic [1,7,8]. This assumption usually is unrealistic because wind tends to be directional, weather gradients exist, host connectivity is patchy, inoculum source strength varies between field and regions, and landscape and terrain features influence transport and deposition of inoculum [29,30]. Anisotropy may occur at multiple spatial scales, ranging from individual plants [31], individual fields [23,32], the mesoscale [33], and the landscape or continental scale [8,34].…”
Section: Discussionmentioning
confidence: 99%
“…(Andersen et al 2019) How do different patterns of cropland connectivity (patterns of cropland proximity that make spread of pathogens more or less likely) influence requirements for regional management? (Margosian et al 2009;Xing et al 2020) How do choices among management types, with adoption influenced by observations of one's own and others' success rates, influence system outcomes?…”
Section: Questions To Be Addressed In Ina 20 and Custom Questionsmentioning
confidence: 99%